Influence of graphene dispersion on the photovoltaic performance of tandem solar cells with four-terminal perovskite–polycrystalline silicon configuration - Noor Fadhilah Ramli; Puteri Nor Aznie Fahsyar; Norasikin Ahmad Ludin; Ahmad Shah Hizam Md Yasir; Suhaila Sepeai (Materials Research Express, 2024)
Silicon’s prominence in photovoltaic technology stems from its abundance and safety. While Si-based solar cells demonstrate high energy conversion efficiency and long-term stability, they encounter challenges such as high costs, intricate fabrication processes, and suboptimal efficiency. To address these issues, researchers have developed tandem solar cells that combine silicon with perovskite cells. This research specifically investigates the use of the spin coating technique with graphene dispersion solutions to deposit graphene layers in perovskite solar cells (PSCs), providing a flexible and cost-effective alternative to conventional methods. By employing graphene as a protective sealant for the perovskite interlayer to prevent degradation, the study aims to enhance the overall performance and stability of tandem solar cells. Graphene was applied onto the hole transport layer at varying concentrations (1, 5, and 10 mg ml ^−1 ) in isopropanol. Notably, the introduction of graphene resulted in decreased power conversion efficiencies (PCEs) in PSC top cells over 60 h, with efficiency reductions of 43%, 24%, and 17% for different concentrations. Importantly, these efficiency declines were significantly lower compared to cells lacking a graphene layer, which experienced a sharp 93% decrease. This investigation underscores the critical role of graphene layers in improving the stability of PSC top cells while maintaining compatibility with the stability of poly-Si bottom cells.